Cardiac connexin-43 and PKC signaling in rats with altered thyroid status without and with omega-3 fatty acids intake - Szeiffová Bačová, B; Egan Beňová, T; Viczenczová, C; Soukup, T; Rauchová, H; Pavelka, S; Knezl, V; Barančík, M; Tribulová, N (Physiological research, 2016)
Thyroid hormones are powerful modulators of heart function and susceptibility to arrhythmias via both genomic and non-genomic actions. We aimed to explore expression of electrical coupling protein connexin-43 (Cx43) in the heart of rats with altered thyroid status and impact of omega-3 polyunsaturated fatty acids (omega-3) supplementation. Adult male Lewis rats were divided into following six groups: euthyroid controls, hyperthyroid (treated with T(3)) and hypothyroid (treated with methimazol) with or without six-weeks lasting supplementation with omega-3 (20 mg/100 g/day). Left and right ventricles, septum and atria were used for immunoblotting of Cx43 and protein kinase C (PKC). Total expression of Cx43 and its phosphorylated forms were significantly increased in all heart regions of hypothyroid rats compared to euthyroid controls. In contrast, the total levels of Cx43 and its functional phosphorylated forms were decreased in atria and left ventricle of hyperthyroid rats. In parallel, the expression of PKC epsilon that phosphorylates Cx43, at serine 368, was increased in hypothyroid but decreased in hyperthyroid rat hearts. Omega-3 intake did not significantly affect either Cx43 or PKC epsilon alterations. In conclusion, there is an inverse relationship between expression of cardiac Cx43 and the levels of circulating thyroid hormones. It appears that increased propensity of hyperthyroid while decreased of hypothyroid individuals to malignant arrhythmias may be in part attributed to the changes in myocardial Cx43.
Keywords: Male; Thyroid Hormones; Fatty Acids, Omega-3; hormony štítné žlázy; hypertyreóza; náhodné rozdělení; srdce; fosforylace; Hyperthyroidism; Myocardium; Phosphorylation; omega-3 mastné kyseliny; mužské pohlaví; Matrix Metalloproteinase 2; proteinkinasa C; potravní doplňky; Dietary Supplements; Animals; matrixová metaloproteinasa 2; Hypothyroidism; zvířata; Rats, Inbred Lew; Random Allocation; potkani inbrední LEW; konexin 43; Connexin 43; Heart; Protein Kinase C; myokard; hypotyreóza